Evaluation Of Cardio-Vascular Risk Factor In Police Officers - ATANU SAHA; SUBHASHIS SAHU; GOUTAM PAUL (International Journal of Pharma and Bio Sciences, 2010)
Police work is one of the most stressful occupations in the world due to their enormous stresses, uncertainty in work, lack of support from the superior, etc. They were suffering from different types of physical and mental disorders. But only a few studies were carried out in India. The present study was conducted to evaluate the cardiovascular status of police officers working in different police stations under the jurisdiction of the superintendent of police, Hooghly district in West Bengal. Apart from questionnaire study, biochemical and physiological study was carried out on police officers and similar number of non-police personnel of same age group to evaluate the cardiovascular risk factors of the police officers. After analyzing the data it was found that the police officers suffer from more cardiovascular risk factors than the general population. Body mass index, blood pressure, cholesterol, triglyceride, High-density lipoprotein were higher than the non-police personnel.